Cassius Dio: The Impact of Violence, War, and Civil War - Lange, Carsten Hjort; Scott, Andrew G. (Historiography of Rome and Its Empire, 2020)
Cassius Dio: The Impact of Violence, War, and Civil War is part of a renewed interest in the Roman historian Cassius Dio. This volume focuses on Dio's approaches to foreign war and stasis as well as civil war. The impact of war on Rome as well as on the history of Rome has long be recognised by scholars, and adding to that, recent years have seen an increasing interest in the impact of civil war on Roman society. Dio's views on violence, war, and civil war are an inter-related part of his overall project, which sought to understand Roman history on its own historical and historiographical terms and within a long-range view of the Roman past that investigated the realities of power.